Erosion modelling in the upper Blue Nile basin: The case of Mizewa watershed in Ethiopia - Assegahegn, M.A.; Zemadim, Birhanu (International Livestock Research Institute, 2013)
The main objective of this research was to study soil erosion and sediment yield in Mizewa watershed using SWAT model. The study was involved hydrological and erosion modelling using primary data collected in the watershed. Hydrological and meteorological data were collected from the stations installed in the watershed by IWMI in collaboration with Ministry of Water and Energy and National Meteorological Service Agency. Suspended sediment data was collected at Mizewa River in the watershed, used for sediment rating curve development. The land use/ land cover map was prepared using field survey and Land sat image and soil map for the watershed was prepared from Abay basin soil as per FAO world soil database. Sensitivity and calibration analysis was done from one year data. Curve number II (cn2) and USLE_P are the most sensitive parameters for flow and sediment, respectively. The model performance test indicated that the coefficient of determination (R2) were 0.84 and 0.83 for flow calibration and validation; 0.82 and 0.81 for sediment calibration and validation, respectively; the Nash Sutcliffe efficiency (NSE) were 0.81 and 0.79 for flow calibration and validation; 0.8 and 0.78 for sediment calibration and validation, respectively. PBIAS is also –18 and –13 for flow calibration and validation and –11.5 and –10.5 for sediment calibration and validation, respectively. The average monthly soil loss was estimated in July with pick suspended sediment concentration despite the pick flow and sediment yield at the outlet were recorded in August which is believed to happen due to the sediment data developed by sediment rating curve. The predicted rate of soil loss and sediment yield at the subbasins and watershed outlet were high which considered the watershed as erosion sensitive area according to Setegn (2009) and Hurni (1985) criteria of erosion sensitivity.